The creation of sustainable human settlement through informal settlement upgrading: the case of Ivory Park, Johannesburg - Nethavhakone, Mukondi Esther (My University, 2010)
The states that participated at the Second United Nations Conference on Human Settlements (Habitat 11), held in Istanbul, Turkey from 3 to 14 June 1996, adopted Habitat Agenda which binds them to the pledge to achieve sustainable human settlements. South Africa, as one of the countries that adopted Habitat Agenda, raised the need to investigate if the adoption of Habitat Agenda in South Africa led to the creation of sustainable human settlements. From the Habitat II it was established that sustainable human settlements can be achieved through informal settlements upgrading. Therefore, this research investigates whether the creation of sustainable human settlements is achieved through the informal settlements upgrading in South Africa, using the case study oflvory Park, Johannesburg. To undertake this investigation a qualitative research method was utilized, whereby the researcher investigates the object of the case study in depth using a variety of data gathering methods to answer research questions. To gather data, three research tools were used namely; in depth interviews, observations and document study. In-depth interviews were conducted with Ivory Park councilors and data from documents and observations were used to support information gathered from interviews. The key finding in this research is that the upgrading process oflvory Park did not lead to the creation of a sustainable human settlement. This is because all elements for the creation of sustainable human settlements have not been fully addressed through the upgrading process of Ivory Park. Many reasons contribute to this situation, however, in the literature it has been stated that the achievement of a sustainable human settlement requires that all elements for the creation of sustainable human settlements are met. However, the informal settlements intervention approach adopted in the upgrading oflvory Park namely 'phased in situ' upgrading approach provides for the achievement of sustainable human settlements. The process of upgrading Ivory Park is slow and it is delaying the transformation to sustainable human settlement. Therefore, the conclusion is that Ivory Park is not yet a sustainable human settlement and if they continue with the same informal settlements intervention approach it will eventually become a sustainable human settlement.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Science in Development Planning. to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2009